Criterios relevantes para establecer el tratamiento contable de la sección 28 beneficios a empleados de la NIIF para pymes (2014)
The implementation of the International Financial Reporting Standard for SMEs allows small and medium sized businesses providing accounting quality and transparency of information, reflecting the accuracy of its financial activities and allowing adequate development of accounting activity also encourages managing a global language for the guild. The application of the IFRS for SMEs to attract potential foreign investments demonstrate the safety and balance of each company; the knowledge and understanding of the accounting treatment for section 28 which deals with employee benefits involves a more detailed management and a change in generally accepted accounting principles, in that section the most appropriate accounting treatment for each type of benefit is established establishing the right time to recognize the work obligation and determining the correct measurement of the benefit to which the worker is entitled in relation to the consideration given by an entity in exchange for services rendered, taking into account the three above criteria may establish the proper application of the accounting standard, allowing the accounting professional to have a broader vision and a more strategic decision-making approach.